Measurement of temperature in the laser heated diamond anvil cell: comparison between reflective and refractive optics. Issue 3 (3rd July 2018) - Giampaoli, Ruggero; Kantor, Innokenty; Mezouar, Mohamed; Boccato, Silvia; Rosa, Angelika D.; Torchio, Raffaella; Garbarino, Gaston; Mathon, Olivier; Pascarelli, Sakura
ABSTRACT: In this article we present a direct comparison between reflective (Schwarzschild mirrors) and refractive (achromatic doublets) optics commonly used in spectroradiometric temperature measurements in laser heated diamond anvil cells. Emission spectra are fitted with the Planck's law and are further analysed with the two-colour technique; theoretical simulations are used to compare the temperature measurement accuracy of the two optical systems. The first result obtained is that achromatic doublets with large numerical aperture (NA ≈ 0.2 ) produce extensive accuracy errors in the full T range (1500–3000 K). When reduced apertures (NA = 0.08 ) are used a good agreement is found with measurements from reflective optics up to 2600 K while systematic differences (around 200 K) appear at higher temperatures. However, these temperature differences cannot explain the discrepancies between the iron melting curves obtained in the past years using laser heated diamond anvil cells.